The Interplay of Host Autophagy and Eukaryotic Pathogens - Evans, Robert J.; Sundaramurthy, Varadharajan; Frickel, Eva-Maria (Frontiers in Cell and Developmental Biology, 2018)
For intracellular pathogens, host cells provide a replicative niche, but are also armed with innate defense mechanisms to combat the intruder. Co-evolution of host and pathogens has produced a complex interplay of host-pathogen interactions during infection, with autophagy emerging as a key player in the recent years. Host autophagy as a degradative process is a significant hindrance to intracellular growth of the pathogens, but also can be subverted by the pathogens to provide support such as nutrients. While the role of host cell autophagy in the pathogenesis mechanisms of several bacterial and viral pathogens have been extensively studied, less is known for eukaryotic pathogens. In this review, we focus on the interplay of host autophagy with the eukaryotic pathogens Plasmodium spp, Toxoplasma, Leishmania spp and the fungal pathogens Candida albicans, Aspergillus fumigatus and Cryptococcus neoformans. The differences between these eukaryotic pathogens in terms of the host cell types they infect, infective strategies and the host responses required to defend against them provide an interesting insight into how they respond to and interact with host cell autophagy. Due to the ability to infect multiple host species and cell types during the course of their usually complex lifestyles, autophagy plays divergent roles even for the same pathogen. The scenario is further compounded since many of the eukaryotic pathogens have their own sets of either complete or partial autophagy machinery. Eukaryotic pathogen-autophagy interplay is thus a complex relationship with many novel insights for the basic understanding of autophagy, and potential for clinical relevance.